Comparison of orbital structures between age-related distance esotropia and acute acquired concomitant esotropia - Jin Hee Kim; Won-Jin Moon; Hyun Jin Shin (PLoS ONE, 2025)
Purpose To compare orbital magnetic resonance imaging (MRI) findings of age-related distance esotropia (ARDE) with those of age-matched healthy controls and acute acquired concomitant esotropia (AACE) patients. Methods Coronal MRI scans of 16 ARDE cases, 15 AACE cases, 26 elderly controls cases, and 22 young controls cases were analyzed to measure (1) the displacement angles of the lateral rectus (LR) and medial rectus (MR), (2) the LR tilting angle, (3) the ratio of the MR-to-LR cross-sectional areas (CSAs), and (4) the superior rectus (SR) downward displacement ratio (SDR). Results ARDE patients showed significant LR sagging relative to elderly controls, by 5.1° (p = 0.048), while there was no significant LR displacement in AACE relative to young controls. ARDE patients also exhibited marked LR tilting relative to all other groups. Additionally, the MR-to-LR CSA ratios were 26% (p = 0.002) and 27% (p = 0.001) higher in the ARDE and AACE groups than in the controls, respectively, indicating imbalance in the horizontal rectus (HR). Additionally, SDR values were higher in ARDE and elderly controls, suggesting that a closer proximity of the SR muscle to the globe is an age-related alteration. Conclusion The findings demonstrate that ARDE is characterized by unique orbital changes, particularly in the LR, that distinguish it from AACE. The observed increase in the MR-to-LR CSA ratio among the esotropia groups points to an imbalance of HR tension. These MRI-based insights enhance our comprehension of the unique pathophysiology of these conditions, helping to distinguish ARDE from AACE in acquired esotropia and guiding customized treatments strategies.